EFEK INFERIORITAS LAYAR TERHADAP KECEPATAN EFEKTIF MEMBACA: STUDI KOMPARATIF MEDIA DIGITAL DAN KERTAS - Rosita Rahma; Faizal Arvianto; Asep Purwo Yudi Utomo (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aimed to examine the effect of screen inferiority on students' effective reading rate (KEM) through a between-subjects experimental design involving 80 students. Data analysis employed descriptive statistics, Welch’s t-test with Cohen's d effect size, Pearson correlation, and hierarchical regression to assess differences, relationships, and the unique contributions of motivation, metacognition, and cognitive load to KEM. The results showed that the paper-media group achieved a mean KEM of 174.51 words per minute, while the digital-media group obtained 154.20 words per minute with an effect size of Cohen's d = 0.267. Intrinsic reading motivation and metacognitive strategy were significantly positively correlated with KEM in both conditions, whereas extraneous cognitive load was negatively correlated, particularly in the digital-media condition. Hierarchical regression analysis revealed that motivation and metacognition explained 18.3% of the variance in KEM beyond the influence of media type. These findings indicate that the screen inferiority effect is moderated by individuals’ metacognitive capacity and intrinsic motivation, rather than uniformly affecting all readers.